Study of Security Analysis With Reference to Anand Rathi Financial Limited - Sarala, K. S.; Tahsin, Arshiya (Indian Journal of Finance, 2009)
An individual saves out of his current income to meet future requirement of funds. He may invest his savings in physical assets like gold, silver, land and building or in the financial assets like securities such as shares, bonds etc. The financial securities deal with the capital market, which include Primary market and Secondary market.